Estetika Visual dan Naratif pada Video Musik "Saat Kau Telah Mengerti" oleh Virgoun: Analisis Komposisi Visual dan Emosi Audiens - Bima Wicaksana, Inovensius Hugo; Prasetyo, Martinus Eko (Jurnal Bahasa Rupa, 2024)
This study aims to analyze the visual and narrative aesthetics in the music video "Saat Kau Telah Mengerti" by Virgoun. The music video serves as a medium for conveying emotions and messages, where visual and narrative elements play a crucial role in shaping audience perceptions. This research employs a qualitative descriptive approach focused on audience meaning, utilizing Edmund Feldman’s formal analysis method through the stages of description, analysis, interpretation, and evaluation. Elements such as composition, lighting, color grading, and camera movement are analyzed to understand how they enhance the audience's emotional experience. The results reveal that these visual elements are effectively utilized to create a profound emotional narrative and strengthen the audience’s connection to the conveyed message. This study provides valuable insights into how visual aesthetics can be leveraged to amplify emotional impact in music videos.